2014
DOI: 10.1111/jam.12521
|View full text |Cite
|
Sign up to set email alerts
|

Cross-talk between probiotic lactobacilli and host immune system

Abstract: SummaryThe mechanism by which probiotic lactobacilli affect the immune system is strain specific. As the immune system is a multicompartmental system, each strain has its way to interact with it and induce a visible and quantifiable effect. This review summarizes the interplay existing between the host immune system and probiotic lactobacilli, that is, with emphasis on lactobacilli as a prototype probiotic genus. Several aspects including the bacterial-host crosstalk with the mucosal and systemic immune system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(62 citation statements)
references
References 126 publications
(228 reference statements)
2
59
1
Order By: Relevance
“…Currently, there is a vast research about the role of specific food components in enhancing immune responses against a challenge with the aim to improve health and reduce disease risks [3]. In this line, the interest in probiotics has substantially increased over the last two decades, which are well-defined as ‘live bacteria that offer a health benefit to the host when administered in adequate amounts’ [4].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is a vast research about the role of specific food components in enhancing immune responses against a challenge with the aim to improve health and reduce disease risks [3]. In this line, the interest in probiotics has substantially increased over the last two decades, which are well-defined as ‘live bacteria that offer a health benefit to the host when administered in adequate amounts’ [4].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was shown that defensins could suppress early events in inflammation and enhance systemic antibody responses 18 . Since several reports have indicated that lactobacilli enhance the production of antimicrobial peptides in mucosal surfaces such as the gut 19 , we examined whether mBD14 could be induced in distant mucosal surfaces (such as gingival tissues) of mice gastrically intubated with LG2055. One week after the onset of gastric intubation with LG2055, significant expression of mBD14-specific mRNA was detected in the small intestine, gingival tissue, and tongue (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has demonstrated that PBio therapy exerts its immunomodulatory effect by regulating signaling through pattern recognition receptors (PRR), including Toll-like receptors (TLRs) (14, 46, 47). In order to better understand the mechanism by which PBio therapy elicits the observed immune changes we describe here, we utilized HEK-293 T cells that had been stably transfected with individual TLRs and a colorimetric reporter gene.…”
Section: Resultsmentioning
confidence: 99%